Assessing The Independent Curriculum In Pkn Learning At Baddoka Sdn Primary School - Wahid, Abdul; Afni, Nur; Hastati, Sri (PT. Hafasy Dwi Nawasena, 2025)
In Indonesia, education cannot be separated from human life. One way to obtain knowledge is the teaching and learning process in schools and this is an implementation of education. To implement the materials or teaching materials used in schools requires something that covers what is called a curriculum. The Merdeka curriculum aims for students to be virtuous, competent and contributive according to their field. This research uses the library research method. The research library used in this research can be books, articles and journals. This research aims to analyze the thevelopment of the education curriculum in Indonesia, especially the development of the curriculum in learning citizenship education (pkn) from the implementation of the 1984 curriculum to the implementation of the Merdeka curriculum. The result of the research concluded that the Merdeka curriculum brought changes in the organization of subjects and the names of citizenship education subjecs, but still had similar educational goals with an approach to make students more active and independent. It is hoped that this research can make a positive contribution in developing more effective citizenship education learning strategies in implementing the independent curriculum at the basic education level